WORKPLACE VIOLENCE AGAINST HEALTHCARE WORKERS – CALL TO ACTION - Marčeta, Elizabeta; Todorović, Jovana (Srpski medicinski časopis Lekarske komore, 2024)
Workplace violence against health workers is common within the healthcare system and yet there seems to be significant underreporting of workplace violence in healthcare. The most common type of workplace violence is verbal abuse. However, there seems to be a significant proportion of physical violence. Perpetrators vary, from patients and their families to co-workers, although less frequently. This article aims to present what workplace violence is, its prevalence, types, consequences, and possible interventions to reduce workplace violence.